Chronic exposure to a low dose of ingested petroleum disrupts corticosterone receptor signalling in a tissue-specific manner in the house sparrow (Passer domesticus). - Romero, L. Michael.; Lattin, Christine R. (Tufts University. Tisch Library., 2016)
Stress-induced concentrations of glucocorticoid hormones (including corticosterone, CORT) can be suppressed by chronic exposure to a low dose of ingested petroleum. However, endocrine-disrupting chemicals could interfere with CORT signalling beyond the disruption of hormone titres, including effects on receptors in different target tissues. In this study, we examined the effects of 6 weeks of exposure to a petroleum laced diet (1% oil weight: food weight) on tissue mass and intracellular CORT receptors in liver, fat, muscle and kidney (metabolic tissues), spleen (an immune tissue) and testes (a reproductive tissue) In the laboratory, male house sparrows were fed either a 1% weathered crude oil (n = 12) or a control diet (n = 12); glucocorticoid receptors and mineralocorticoid receptors were quantified using radioligand binding assays. In oil exposed birds, glucocorticoid receptors were lower in one metabolic tissue (liver), higher in another metabolic tissue (fat) and unchanged in four other tissues (kidney, muscle, spleen and testes) compared with control birds. We saw no differences in mineralocorticoid receptors between groups. We also saw a trend towards reduced mass of the testes in oil-exposed birds compared with controls, but no differences in fat, kidney, liver, muscle or spleen mass between the two groups. This is the first study to examine the effects of petroleum on CORT receptor density in more than one or two target tissues. Given that a chronic low dose of ingested petroleum can affect stress-induced CORT titres as well as receptor density, this demonstrates that oil can act at multiple levels to disrupt an animal's response to environmental stressors. This also highlights the potential usefulness of the stress response as a bioindicator of chronic crude oil exposure.